Evaluation of Tensile and Thermal Behavior Analysis of Nano Carbon Fiber Reinforced Polymer Composite - Vinod Kumar, T; Chandrasekaran, M; Vivek, P; Vairavel, M (International Journal of Engineering and Technology, 2018)
Today a lot of research work is performed throughout the world on the use of natural fibers as a strengthening material introduced in the preparation of various kinds of composites, and also the use of natural fiber/polymer composites in civil and mechanical engineering fields are playing very important role due to its usage of natural resource and its properties. From the current journal, we have recently found NFRPC fibers which are extracted from NFRPC plants by involving hard physical work. In this journal, the tensile components of the six to seven months NFRPCare analyzed through various tests such as FTIR, XRD, SEM, THERMO GRAVIMETRIC ANALYSE and match with other available conventional all-natural fibers, and also examine the chemical qualities of NFRPC. The fiber of NFRPC has a high wax content, so it's easy to bind with materials like resin. SEM analyze also signifies the presence of voids on the interior surface of the fiber material. and the results show that the NFRPC provides good Tensile and Thermal properties.Â Â